Monochorionic-Triamniotic Triplet Pregnancy Complicated by Twin Reversed Arterial Perfusion Sequence: Case Report and Literature Review - Pan, Pingshan; Luo, Guoyang; Tang, Lu; Rolle, Jeanne D.; Qin, Yuqin; Zeng, Quan; Wei, Jiangting; Chen, Yuanfang; Wei, Hongwei (American Journal of Perinatology Reports, 2017)
Background Monochorionic-triamniotic pregnancies are rare and fraught with complications.Case A case of monochorionic-triamniotic triplet pregnancy complicated by twin reversed arterial perfusion (TRAP) sequence is presented. The patient declined termination or selective fetal reduction. Triplet C was acardiac. At 24 weeks, triplet B developed polyhydramnios. At 30 weeks, polyhydramnios was seen in all three amniotic sacs, but without signs of fetal hydrops and with normal Doppler velocimetry measurements in the umbilical artery, middle cerebral artery, and ductus arteriosus of triplets A and B. At 322/7 weeks, the patient presented with preterm premature rupture of membranes and preterm labor. Two live male infants were delivered by cesarean delivery weighing 1,350 and 1,390 g, respectively; the acardiac fetus weighed 1,460 g. Pathology examination revealed a single placenta weighing1,250 g, with evidence of direct vascular connections between triplets A and C as well as between triplets A and B.Conclusion Monochorionic-triamniotic triplet pregnancy with TRAP sequence is rare. Although the risk of complications is high, such pregnancies can be managed conservatively in select cases.
Keywords: monochorionic; triplet pregnancy; acardiac fetus; twin-reversed arterial perfusion sequence